Pengaruh Customer Experience, Kualitas Produk, Price Terhadap Keputusan Pembelian Mixue Di Palembang - Putri Maretha, Wina; Purnamasari, Endah Dewi; Yeni, Yeni (Value : Jurnal Manajemen dan Akuntansi, 2025)
In an era of rapid technological advancement, the food and beverage sector faces increasingly intense competition, requiring companies to adopt effective methods to attract consumer interest. This study aims to examine the impact of Customer Experience, Product Quality, and Price on the Purchase Decision of Mixue Ice Cream in Palembang, specifically targeting students from the Faculty of Economics at Universitas Indo Global Mandiri. The research population consisted of 409 Management students from the 2021–2023 cohorts, with a sample size of 202 respondents determined using the Slovin formula and a simple random sampling method. This study employed a quantitative methodology, utilizing data collected through surveys and analyzed using multiple linear regression with SPSS version 25. The evaluation included tests for validity, reliability, and classical assumption evaluations, including normality, multicollinearity, and heteroscedasticity. The findings indicate that both partially and simultaneously, Customer Experience, Product Quality, and Price have a positive and significant influence on the Purchase Decision of Mixue Ice Cream. These results suggest that highly satisfying customer experiences, superior product quality, and competitive pricing are critical determinants of consumer purchasing decisions; thus, marketing strategies that emphasize these three elements can enhance a company's competitiveness in an increasingly tight market.